Innovation or Fraud? The Modus Operandi of Investment Startups and the Voidance of the Business Judgment Rule - Aditya, Lucky Elza; Widodo, Kartika Youri; Musyarri, Fazal Akmal; Putri, Nabilla Desyalika (Jurnal Analisis Hukum, 2026)
The rapid expansion of digital investment startups in Indonesia has contributed significantly to economic growth and financial inclusion. However, this development has also given rise to serious allegations of misconduct in the management of public funds. Cases involving eFishery, Investree, TaniHub, and Akseleran reveal indications of financial statement manipulation, conflicts of interest, non-transparent fundraising practices, and failures in risk management. These circumstances raise complex legal questions concerning the boundary between legitimate business misjudgment and corporate economic crime. This study aims to normatively examine whether the conduct of digital investment startups remains protected under the Business Judgment Rule (BJR) or instead fulfills the legal elements of economic criminal offenses. The research employs a normative legal methodology, incorporating statutory, conceptual, and case-based approaches. The findings indicate that practices such as financial statement manipulation, fictitious transactions and borrowers, and the concealment of material information constitute structured fraudulent conduct that effectively nullifies the protection afforded by the BJR. The principal contribution of this study lies in articulating a clearer doctrinal boundary between permissible business risk and digital economic crime, while strengthening the legal foundation for the application of corporate criminal liability to digital investment startups.